Prehospital Application of Hemostatic Agents in Iraq and Afghanistan. (3rd September 2018) - Schauer, Steven G.; April, Michael D.; Naylor, Jason F.; Maddry, Joseph K.; Arana, Allyson A.; Dubick, Michael A.; Fisher, Andrew D.; Cunningham, Cord W.; Pusateri, Anthony E.
Abstract: Introduction : Hemorrhage is the leading cause of death on the battlefield. Development of chitosan- and kaolin-based hemostatic agents has improved hemorrhage control options. Sparse data exists on the use of these agents in the prehospital, combat setting. We describe recent use of these agents and compare patients receiving hemostatic to the baseline population.Methods : We used a series of emergency department (ED) procedure codes to identify patients within the Department of Defense Trauma Registry (DODTR) from January 2007 to August 2016. We only included patients for whom the DODTR specified the hemostatic agent utilized (chitosan or kaolin). We defined a serious injury by body region as an Abbreviated Injury Score (AIS) of 3 or greater.Results : Our predefined search codes captured 28, 222 patients. Of those, 258 (0.9%) patients had documented hemostatic use: 58 chitosan, 201 kaolin, and one subject received both. Patients undergoing hemostatic agent application were more likely to be injured by gunshot wound or explosive. Patients with hemostatic application had higher median composite Injury Severity Scores (10 vs. 9, p < 0.001), and higher AIS for the abdomen, extremity and superficial body regions with higher rates of blood product utilization. Proportions of patients suffering traumatic amputations and undergoing tourniquet application were higher in the hemostatic agent group than the baseline population (11.6% vs. 6.7%, p = 0.002 and 43.4% vs. 13.8%, p < 0.001, respectively).Conclusions : Hemostatic agents were infrequently utilized to manage traumatic hemorrhage during the recent conflicts in Afghanistan and Iraq. Hemostatic agent use was more frequent in casualties with gunshot wounds, traumatic amputations, concomitant tourniquet application, and greater blood product administration."